Upaya Pemerintah Daerah Dalam Pengembangan Potensi Pariwisata - Willy Tri Hardianto; Felika Agesti Yolanda; Ignatius Adiwidjaja (Universitas Islam Malang, 2020)
The development of tourism sector must be supported by a professional government servicing that has an impact on the increasing of local revenue, expanding employment, attracting investors, and a promotional event to introduce the cultural history of the region to the people outside Batu City. The qualitative design was carried out in this present study through a purposive sampling. Then, the data were called together using interviews and observations. The results revealed that providing opportunities for investors to contribute developing tourism sector was promptly done by government. Moreover, it was guided by the established service standards towards the needs of visitors. Another supporting factors were about the citizen participation, the affordable costs, and the complete tourism infrastructure that have been in accordance with the policy of government in Batu City.